Renal Manifestations of Tuberous Sclerosis Complex: Key Findings From the Final Analysis of the TOSCA Study Focussing Mainly on Renal Angiomyolipomas - Kingswood, J. Chris; Belousova, Elena; Benedik, Mirjana P.; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; Beaure d'Augères, Guillaume; de Vries, Petrus J.; Ferreira, José C.; Feucht, Martha; et al. (Frontiers in Neurology, 2020)
Renal angiomyolipomas are one of the most common renal manifestations in patients with TSC, with potentially life-threatening complications and a poor prognosis. Despite the considerable progress in understanding TSC-associated renal angiomyolipomas, there are no large scale real-world data. The aim of our present study was to describe in detail the prevalence and outcome of renal angiomyolipomas in patients with TSC, enrolled into the TOSCA. We also sought to evaluate the relationship of TSC-associated renal angiomyolipomas with age, gender and genotype. The potential risk factors for renal angiomyolipoma-related bleeding and chronic kidney disease (CKD) were studied. Of the 2211 eligible patients, 1062 (48%) reported a history of renal angiomyolipomas. The median age of diagnosis of renal angiomyolipoma in the 1062 patients was 13 years. Renal angiomyolipomas were significantly more prevalent in female patients (p<0.0001). Rates of angiomyolipomas >3cm (p=0.0119), growing lesions (p=0.0439) and interventions for angiomyolipomas (p=0.0058) were also higher in females than males. Pre-emptive intervention for renal angiomyolipomas with embolisation, surgery, or mTOR inhibitor may have abolished the gender difference in impaired renal function, hypertension and other complications. The rate of interventions for angiomyolipomas was less common in children than in adults, but interventions were reported in all age groups. In the substudy of 76 patients the complication rate was too low to be useful in predicting risk for more severe CKD. In addition, in this substudy no patient had a renal haemorrhage after commencing on an mTOR inhibitor. Our findings confirmed that renal angiomyolipomas in subjects with TSC1 mutations develop on average at the later age, are relatively smaller in size and less likely to be growing; however, by age 40 years, no difference was observed in the percentage of patients with TSC1 and TSC2 mutations needing intervention. The peak of appearance of new renal angiomyolipomas was observed in patients aged between 18-40 years, but, given that angiomyolipomas can occur later, lifelong surveillance is necessary. We found that pre-emptive intervention was dramatically successful in altering the outcome compared to historical controls; with high pre-emptive intervention rates but low rates of bleeding and other complications.